EXPANSION AND ELECTRIFICATION OF THE PUBLIC TRANSPORT SYSTEM IN CURITIBA, PR: AN ANALYSIS BASED ON SDG - 11 AND THE TRANSFORMATIVE INNOVATION POLICIES (TIP) - Doliveira, Sérgio Luis Dias; Cunha, Sieglinde Kindl da; Massuga, Flavia (Brazilian Journal of Management and Innovation (Revista Brasileira de Gestão e Inovação), 2023)
Objective: The main objective of this study is to describe the project to improve and electrify the Inter Line 2 of the Integrated Transport Network in the city of Curitiba-PR, in order to understand its compliance with the requirements of the SDG-11, target 11.2 and the relationship with transformative results from Transformative Innovation Policies (TIP) in a context of socio-technical transitions. Methodology: It is a descriptive and exploratory study of mixed approach, using documents, diagnosis materials, and semistructured interviews. The data were assessed through content analysis. Originality/Relevance: Cities correspond to places with great urgency for change. Understanding transition initiatives and associated TIPs is necessary to encourage the transformation to more sustainable ways of life in urban centers. Results: The results show that the expansion and electrification project for the Inter Line 2 is in accordance with target 11.2 of SDG-11 and will provide improvements in the quality of life for the population of the entire metropolitan area. Moreover, it corresponds to a strong niche of socio-technical transformation and its benefits are configured as a transformative result in accordance with the TIP. Theoretical and Methodological Implications: The study’s theoretical contribution illustrates the TIPs theory from the transition perspective, presenting an innovative project that meets the SDGs and configures itself as a transformative result in the socio-technical urban mobility system. Social contributions to management: It also serves as an example for other urban centers with regard to the establishment of public policies aimed at sustainability.